EXPLORING THE IMPACT OF MODIFIED PRENATAL YOGA ON EMOTIONAL WELL-BEING AMONG THIRD-TRIMESTER PREGNANT WOMEN: A QUALITATIVE PHENOMENOLOGICAL STUDY - Yunita Laila Astuti; Masita Masita; Abdullah Antaria; Fitrah Ivana Paisal; Vina Dwi Wahyunita (Jurnal Manajemen Kesehatan Indonesia, 2026)
Third-trimester anxiety affects 28–34% of pregnant women globally and is associated with adverse birth outcomes. Prenatal yoga represents a promising non-pharmacological intervention, yet qualitative evidence exploring women's lived experiences remains limited. This study aimed to explore the impact of modified prenatal yoga on emotional well-being among third-trimester pregnant women through phenomenological inquiry. A qualitative phenomenological design was employed with ten purposively sampled third-trimester pregnant women attending prenatal yoga classes at Pondok Labu Primary Health Center, Jakarta. Data were collected via in-depth semi-structured interviews, participant observation, and document review, then analysed using Braun and Clarke's six-phase thematic analysis. Five interconnected themes emerged: (1) enhanced calmness and emotional regulation through mind-body integration; (2) deepened maternal-fetal bonding facilitated by mindful awareness; (3) cognitive reframing and enhanced childbirth self-efficacy through positive affirmations; (4) holistic wellness integration addressing physical-emotional-spiritual dimensions; and (5) perceived program value and sustainability expectations. Participants reported transformative experiences characterized by anxiety reduction, increased confidence, and strengthened maternal identity. Modified prenatal yoga positively influences third-trimester emotional well-being through multidimensional mechanisms encompassing physiological relaxation, cognitive restructuring, and relational bonding. These findings support integration of prenatal yoga as a routine component of primary maternity care to address perinatal mental health needs.Keywords: prenatal yoga, emotional, qualitative, third trimester, maternal mental health, phenomenology